On a new marine podocopid genus and species (Ostracoda: Hemicytheridae) from Brazil - Coimbra, João Carlos; Morais, Anderson L.m. De (Zootaxa, 2016)
Bulbocythere calida gen. et sp. nov., a benthic marine ostracode, is herein described and illustrated. The geographic and bathymetric distributions of this new taxon are based on the analysis of 923 bottom samples collected along the entire Brazilian continental shelf in a depth range of about 11 to 280 m, plus sediments of 176 samples from the Sepetiba Bay and 37 samples from the Tamandaré Bay. In the study material, this ostracode was rare, and restricted to the warm waters of the E and NE shelves and to the substrates around the reefs of the Tamandaré Bay.